The influence of financial performance on profitability of sharia commercial banks in Indonesia using the CAMEL method - Minarni; Abidin, Munirul; Ekowati, Vivin Maharani (Universitas Islam Indonesia, 2023)
IntroductionResearch on Islamic commercial banks in Indonesia have been extensively conducted, with a focus on banks in general and large banks. However, research specifically targeting medium-sized banks, namely PT Bank Muamalat Indonesia, PT Bank Mega Syariah, PT Bank Panin Dubai Syariah, PT Bank BCA Syariah, and PT Bank KB Bukopin Syariah, is still limited.ObjectivesThis study aims to examine the influence of the financial performance of Islamic banks on their profitability using the CAMEL indicator.MethodThis research is quantitative with a correlational approach. The population in this study consists of 12 Islamic commercial banks in Indonesia, with 5 of them selected as samples. The sampling technique used is purposive sampling. The study utilizes secondary data from quarterly financial ratio reports of Islamic banks published by the Financial Services Authority (OJK). The analysis involves evaluating the impact of CAR, NPF, NOM, BOPO, and FDR on ROA using multiple linear regression analysis.ResultsThe findings indicate that, partially, CAR and NPF do not significantly affect the ROA of Islamic banks. However, NOM, BOPO, and FDR have a significant impact on the ROA of Islamic banks.Implicationsthe research motivates Islamic bank management to improve their financial ratios to meet the health criteria set by Bank Indonesia (BI) and OJK. Maintaining healthy financial ratios has implications for the level of trust that customers and potential customers have in Islamic banks and ultimately determines the long-term existence of these banks.Originality/NoveltyThis study contributes to the development of risk management theory by examining the factors influencing the fluctuations in the values of CAR, NPF, NOM, BOPO, and FDR on the ROA of Islamic banks.